Enhanced Electrochemical Capacity of Spherical Co‐Free Li1.2Mn0.6Ni0.2O2 Particles after a Water and Acid Treatment and its Influence on the Initial Gas Evolution Behavior. Issue 20 (8th September 2022) - Klein, Florian; Bansmann, Joachim; Jusys, Zenonas; Pfeifer, Claudia; Scheitenberger, Philipp; Mundszinger, Manuel; Geiger, Dorin; Biskupek, Johannes; Kaiser, Ute; Behm, R. Jürgen; Lindén, Mika; Wohlfahrt‐Mehrens, Margret; et al.
Abstract: Li‐rich layered oxides (LRLO) with specific energies beyond 900 Wh kg −1 are one promising class of high‐energy cathode materials. Their high Mn‐content allows reducing both costs and the environmental footprint. In this work, Co‐free Li1.2 Mn0.6 Ni0.2 O2 was investigated. A simple water and acid treatment step followed by a thermal treatment was applied to the LRLO to reduce surface impurities and to establish an artificial cathode electrolyte interface. Samples treated at 300 °C show an improved cycling behavior with specific first cycle capacities of up to 272 mAh g −1, whereas powders treated at 900 °C were electrochemically deactivated due to major structural changes of the active compounds. Surface sensitive analytical methods were used to characterize the structural and chemical changes compared to the bulk material. Online DEMS measurements were conducted to get a deeper understanding of the effect of the treatment strategy on O2 and CO2 evolution during electrochemical cycling. Abstract : Surface treatment : Co‐free Li1.2 Mn0.6 Ni0.2 O2 cathode material was treated with acid or water to modify the surface. A subsequent calcination step at lower temperature provided materials with high capacity (up to 270 mAh g ‐1 ) and cycling stability, whereas high temperatures lead to deactivation.